Training to improve the capacity of posyandu toddler cadres in early detection of stunting - Luluk Khusnul Dwihestie; Allania Hanung Putri Sekar Ningrum; Fitriana Mustikaningrum (Community Empowerment, 2024)
Early detection of stunting is crucial to optimize the role of posyandu cadres in comprehensive stunting prevention, including anthropometric measurements, result interpretation, documentation, and education for parents. The problem in Randusari Village is the low level of knowledge among cadres regarding early detection of stunting, especially related to accurate height measurement and providing education on fulfilling toddler nutrition. This community service aimed to improve the capacity of posyandu cadres in Randusari Village through structured training. The methods used in this activity were lectures, discussions, role-playing, and evaluation. The results of the training showed a significant increase in cadres' understanding of early detection of stunting and IEC skills. This training successfully improved the cadres' ability to participate in stunting prevention and reduction efforts in Randusari Village. Furthermore, the cadres were facilitated with educational media in the form of food models and “Cegah Stunting” booklets to facilitate the dissemination of the stunting reduction acceleration program in Boyolali Regency.